A case study exploring employment factors affecting general practice nurse role development. Issue 1 (29th June 2015) - Crossman, Sue; Pfeil, Michael; Moore, Jennifer; Howe, Amanda
Abstract : Aim: The aim of this study was to explore the factors affecting role development in practice nursing in the United Kingdom. Background: General practice is currently central to National Health Service reform, producing favourable conditions for the practice nurse role to be further strengthened and developed. However, the literature has continued to describe evidence that practice nurses are a disempowered, isolated group with many constraints reducing their ability to respond to opportunities to develop their role. The rationale for conducting the study was therefore to provide a greater understanding about the constraining factors and their influence on practice nurses wishing to develop their role. Method: The method used to conduct the research followed a case approach, as the subject being investigated was complex with multiple inter-related factors and the approach was exploratory. The cases comprised six UK general practices and the participants within each case were a practice nurse, a GP and a practice manager. Findings: A combination of factors was found to contribute to the way the practice nurse role evolves. These are education, practice culture, practice nurse personal characteristics and empowerment. Empowerment holds the key to maximising the conditions favourable to practice nurse role evolution. This is not, however, a 'single' factor; it represents the combined synergistic effects of practice culture and practice nurse personal characteristics on creating an empowering environment. The inter-relationship between these was captured in a framework and given the title 'empowering employment principles'. Conclusion: The 'empowering employment principles' illustrate the features most conducive to role evolution, thus providing a tool for practice nurses and their employers to enhance opportunities for nurses to develop their role.